Classified [compact disc, unabridged] - Michaels, Fern (Michaels, Fern. Godmothers, 2013)
Teresa 'Toots' Amelia Loudenberry is a wealthy woman by anyone's standards. But the riches that mean most to her are the loving friends and family she's accumulated over the course of a life well lived. Toots's friendship with Dr. Phil Becker has grown unexpectedly close, and that brings both joy and complications. It's one thing for a lady to be a little vague about her age, but Toots hasn't been entirely honest with Phil about the number of marriages in her past.